A modified separator, its preparation method and application

CN116979220BActive Publication Date: 2026-10-27DONGGUAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311070604.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2026-10-27
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

但是,聚烯烃材料是热塑性高分子材料,其尺寸稳定性相对较差,当温度高于软化点时会发生热收缩,甚至熔融

Benefits of technology

[0026]本发明提供了一种改性隔膜,包括聚烯烃高分子薄膜基体和负载在所述聚烯烃高分子薄膜基体上的聚氧化乙烯聚合物和二氧化钛纳米颗粒;所述聚氧化乙烯聚合物具有三维网状结构。本发明利用PEO三维网络聚合物和二氧化钛纳米颗粒对薄膜基体进行改性,将无机物掺杂与有机聚合物网络结合,通过形成异质界面的方式,产生内建电场,不仅能够增强薄膜基体的表面机械性能、浸润性,提高薄膜基体的热稳定性和机械尺寸稳定性;同时还能够保证获得高的锂离子迁移和导电能力,从而提高锂离子电导率,增强锂离子电池的综合性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116979220B_ABST
    Figure CN116979220B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion batteries, and particularly relates to a modified diaphragm and a preparation method and application thereof. The application provides a modified diaphragm, which comprises a polyolefin high molecular film matrix and polyethylene oxide polymer and titanium dioxide nanoparticles loaded on the polyolefin high molecular film matrix; the polyethylene oxide polymer has a three-dimensional network structure. The application modifies the film matrix by using the PEO three-dimensional network polymer and titanium dioxide nanoparticles, combines inorganic doping and organic polymer network, forms a hetero-interface mode, generates an internal built-in electric field, can not only enhance the surface mechanical properties and wettability of the film matrix, improve the thermal stability and mechanical size stability of the film matrix, but also can ensure high lithium ion migration and conductivity, thereby improving the lithium ion conductivity and enhancing the comprehensive performance of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a modified separator, its preparation method, and its application. Background Technology

[0002] Lithium-ion batteries, as electrochemical energy storage devices, have been widely used in energy storage fields such as new energy vehicles, portable electronic devices, and new clean energy technologies. A lithium-ion battery consists of components such as a positive electrode material, a negative electrode material, a separator, and an electrolyte. The separator, as a key component of the battery, is known as the "third electrode." Its main function is to isolate the positive and negative electrodes, while also serving as a channel for ion transport. It has a significant impact on the battery's internal resistance, capacity, safety performance, and storage performance.

[0003] Polyolefin materials (such as polypropylene and PP) have become the preferred choice for preparing lithium-ion battery separators due to their excellent processing performance, good mechanical properties, stable chemical properties, and low cost. However, polyolefin materials are thermoplastic polymers with relatively poor dimensional stability. They undergo thermal shrinkage and even melting when the temperature exceeds their softening point. Moreover, polyolefin materials are non-polar polymers with poor electrolyte wettability, leading to higher internal resistance, lower ion mobility, and lower lithium-ion conductivity, thus hindering the full performance of lithium-ion batteries. Summary of the Invention

[0004] The purpose of this invention is to provide a modified separator, its preparation method and application. The modified separator provided by this invention has excellent dimensional stability and high conductivity, and exhibits excellent electrochemical performance when applied to lithium-ion batteries.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] This invention provides a modified membrane comprising a polyolefin polymer film matrix and a polyethylene oxide polymer and titanium dioxide nanoparticles loaded on the polyolefin polymer film matrix.

[0007] The polyethylene oxide polymer has a three-dimensional network structure.

[0008] Preferably, the loading percentage of the polyethylene oxide polymer is 1.878–3.878%; and the loading percentage of the titanium dioxide nanoparticles is 0.256–0.356%.

[0009] Preferably, the polyolefin polymer film matrix includes PP film or PE film.

[0010] The present invention also provides a method for preparing the modified diaphragm described in the above technical solution, comprising the following steps:

[0011] A coating solution is obtained by mixing polyethylene glycol diacrylate, an initiator, a titanium source, a polar organic solvent, and water.

[0012] The coating liquid is coated onto the surface of a polyolefin polymer film substrate and then heat-treated to obtain the modified diaphragm.

[0013] Preferably, the initiator includes azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, hydrogen peroxide, potassium persulfate, or benzoyl peroxide;

[0014] The mass of the initiator is 4 to 6% of the mass of the polyethylene glycol diacrylate.

[0015] Preferably, the polar organic solvent includes acetone, acetonitrile, or chloroform;

[0016] The ratio of polyethylene glycol diacrylate to polar organic solvent is 1g:150mL;

[0017] The volume ratio of the polar organic solvent to water is 150:5 to 10.

[0018] Preferably, the titanium source includes tetraethyl titanate, tetrabutyl titanate, titanium n-propoxide, titanium tetraisopropoxide, or titanium tetramethanol.

[0019] The mass ratio of the titanium source to polyethylene glycol diacrylate is 0.22 to 0.62:1.

[0020] Preferably, the mixture includes:

[0021] A first mixture is prepared by first mixing polyethylene glycol diacrylate, an initiator, and a polar organic solvent to obtain a first mixture.

[0022] The first mixture is then mixed with water to obtain a second mixture.

[0023] The second mixture and the third titanium source are mixed.

[0024] Preferably, the heat treatment temperature is 59–61°C and the time is 5–6 hours.

[0025] The present invention also provides the application of the modified separator described in the above technical solution or the modified separator prepared by the preparation method described in the above technical solution in lithium-ion batteries.

[0026] This invention provides a modified separator, comprising a polyolefin polymer film matrix and polyethylene oxide polymer and titanium dioxide nanoparticles loaded on the polyolefin polymer film matrix; the polyethylene oxide polymer has a three-dimensional network structure. This invention utilizes the PEO three-dimensional network polymer and titanium dioxide nanoparticles to modify the film matrix, combining inorganic doping with an organic polymer network. By forming a heterogeneous interface, a built-in electric field is generated, which not only enhances the surface mechanical properties and wettability of the film matrix, and improves its thermal and dimensional stability, but also ensures high lithium-ion migration and conductivity, thereby improving lithium-ion conductivity and enhancing the overall performance of the lithium-ion battery. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of the structure of the modified diaphragm obtained in Example 1;

[0028] Figure 2 This is a schematic diagram of the process flow for Example 1;

[0029] Figure 3 SEM images of the modified diaphragm and pure PP film substrate obtained in Example 1 and Comparative Example 1;

[0030] Figure 4 The images show the wetting angle test results of the modified diaphragm and pure PP film substrate obtained in Example 1 and Comparative Example 1.

[0031] Figure 5 The tensile properties test diagrams are of the modified diaphragm and pure PP film substrate obtained in Example 1 and Comparative Example 1.

[0032] Figure 6 The figures show the room temperature conductivity of the modified diaphragm and the pure PP film substrate obtained in Example 1 and Comparative Example 1. Detailed Implementation

[0033] This invention provides a modified membrane comprising a polyolefin polymer film matrix and a polyethylene oxide polymer and titanium dioxide nanoparticles loaded on the polyolefin polymer film matrix.

[0034] The polyethylene oxide polymer has a three-dimensional network structure.

[0035] In this invention, the polyolefin polymer film substrate preferably comprises a PP film or a PE film. This invention does not impose any particular limitation on the thickness of the polyolefin polymer film substrate; any thickness known to those skilled in the art can be used.

[0036] In this invention, the polyethylene oxide polymer (PEO) has a three-dimensional network structure. In this invention, the loading percentage of the polyethylene oxide polymer is preferably 1.878% to 3.878%, more preferably 2.878%. In this invention, the loading percentage of the titanium dioxide nanoparticles is preferably 0.256% to 0.356%, more preferably 0.306%.

[0037] The present invention also provides a method for preparing the modified diaphragm described in the above technical solution, comprising the following steps:

[0038] A coating solution is obtained by mixing polyethylene glycol diacrylate, an initiator, a titanium source, a polar organic solvent, and water.

[0039] The coating liquid is coated onto the surface of a polyolefin polymer film substrate and then heat-treated to obtain the modified diaphragm.

[0040] In this invention, unless otherwise specified, all raw materials used in the preparation are commercially available products well known to those skilled in the art.

[0041] The present invention mixes polyethylene glycol diacrylate (PEGDA), an initiator, a titanium source, a polar organic solvent and water to obtain a coating solution.

[0042] In this invention, the initiator preferably includes azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, hydrogen peroxide, potassium persulfate, or benzoyl peroxide. In this invention, the mass of the initiator is preferably 4-6% of the mass of the polyethylene glycol diacrylate, more preferably 5%.

[0043] In this invention, the polar organic solvent preferably includes acetone, acetonitrile, or chloroform; the preferred volume ratio of polyethylene glycol diacrylate to the polar organic solvent is 1 g: 150 mL. In this invention, the water is preferably deionized water; the preferred volume ratio of the polar organic solvent to water is 150: 5 to 10.

[0044] In this invention, the titanium source preferably includes tetraethyl titanate, tetrabutyl titanate, titanium n-propoxide, titanium tetraisopropoxide, or titanium tetramethylethanol; the mass ratio of the titanium source to polyethylene glycol diacrylate is preferably 0.22 to 0.62:1, more preferably 0.42:1.

[0045] In this invention, the mixing preferably includes: mixing polyethylene glycol diacrylate, an initiator, and a polar organic solvent to obtain a first mixture;

[0046] The first mixture is then mixed with water to obtain a second mixture.

[0047] The second mixture and the third titanium source are mixed.

[0048] In this invention, both the first and second mixing are preferably carried out under stirring conditions. The stirring speed is not particularly limited in this invention; any speed well known to those skilled in the art can be used. In this invention, the first mixing time is preferably 20–30 minutes. In this invention, the second mixing time is preferably 20–30 minutes.

[0049] In this invention, the third mixing method is preferably as follows: the titanium source is added dropwise to the second mixture under stirring conditions, followed by continuous stirring. This invention does not impose any particular limitation on the dropwise addition rate; any rate well-known to those skilled in the art can be used. In this invention, the continuous stirring is preferably carried out under closed conditions; the continuous stirring time is preferably 6–7 hours.

[0050] After obtaining the coating liquid, the present invention coats the coating liquid onto the surface of a polyolefin polymer film substrate and performs heat treatment to obtain the modified diaphragm.

[0051] The present invention does not impose any particular limitation on the coating method, and any method known to those skilled in the art can be used. In a specific embodiment of the present invention, the coating process is preferably as follows: the polyolefin polymer film substrate is fixed on a glass plate, a coating liquid is transferred onto the polyolefin polymer film substrate using a pipette, and a coating is applied evenly using a scraper, and this process is repeated twice; then the above coating process is repeated on the other side of the polyolefin polymer film substrate.

[0052] After coating, the present invention preferably includes drying the resulting wet coating.

[0053] In this invention, the heat treatment temperature is preferably 59–61°C, more preferably 60°C; the time is preferably 5–6 hours. In this invention, the heat treatment is preferably carried out in a vacuum drying oven.

[0054] The present invention also provides the application of the modified separator described in the above technical solution or the modified separator prepared by the preparation method described in the above technical solution in lithium-ion batteries.

[0055] To further illustrate the present invention, a modified diaphragm, its preparation method, and its application are described in detail below with reference to the accompanying drawings and embodiments. However, these descriptions should not be construed as limiting the scope of protection of the present invention.

[0056] Example 1

[0057] Mix 0.2g PEGDA, 0.01g initiator AIBN and 30mL acetone, stir for 20min, then add 8mL deionized water dropwise, and stir again for 20min to obtain the mixture.

[0058] Then, 0.084 g of tetraethyl titanate was slowly added dropwise to the mixture obtained above, the container was sealed, and the mixture was stirred for 6 hours until a uniform coating solution was obtained.

[0059] The PP film substrate was fixed on a glass plate, and 1.7 mL of coating liquid was transferred onto the film substrate using a pipette. The coating was then applied evenly using a scraper, and the process was repeated twice. The same coating process was then repeated on the other side of the film.

[0060] After the wet mill was dried, it was placed in a vacuum drying oven and heat-treated at 60°C for 5 hours to obtain the modified diaphragm, wherein the loading mass percentage of PEO was 2.878% and the loading mass percentage of titanium dioxide nanoparticles was 0.306%.

[0061] The structural schematic diagram of the modified diaphragm obtained in this embodiment is shown below. Figure 1 As shown in the diagram, the process flow chart is as follows: Figure 2 As shown.

[0062] Comparative Example 1

[0063] The modified membrane was prepared in accordance with the method of Example 1, except that the modified membrane did not contain titanium dioxide nanoparticles.

[0064] Performance testing

[0065] Test Example 1

[0066] Scanning electron microscopy (SEM) was performed on the modified diaphragm and pure PP film substrate obtained in Example 1 and Comparative Example 1; the resulting test images are shown below. Figure 3 As shown; where (a) is a pure PP film substrate, (b) is Comparative Example 1, and (c) is Example 1;

[0067] from Figure 3 It can be seen that after PEGDA polymerization, a polymer network structure is formed on the surface of the PP film matrix, which fills some porous structures. At the same time, TiO2 inorganic nanoparticles obtained by in-situ method also appear on the surface of the PP film, confirming that the polymer network and inorganic nanoparticles have been successfully distributed in the surface structure of the PP film by experimental methods.

[0068] Test Example 2

[0069] The wetting angles of the modified diaphragm and pure PP film substrate obtained in Example 1 and Comparative Example 1 were tested, and the test results are shown in the figure below. Figure 4 As shown, (a) is a pure PP film substrate, (b) is Comparative Example 1, and (c) is Example 1;

[0070] from Figure 4It can be seen that, compared with the two modified separators in Example 1 and Comparative Example 1, the PP film substrate has the largest wetting angle (i.e., 89.96° and 87.90°). With the formation of the polymer network PEO and the introduction of inorganic TiO2 nanoparticles, the wetting angle of the PP film substrate is significantly reduced, which is beneficial for the wetting of the electrolyte. Among them, the modified separator obtained in Example 1 has the smallest wetting angle (i.e., 83.37° and 83.56°). When this separator is used as a lithium-ion battery separator, it has the strongest wettability of electrolyte, which is conducive to the rapid migration and conduction of lithium ions in the pores of the membrane, reducing the resistance of the wetted membrane, improving its conductivity, and enhancing the electrochemical performance of the lithium battery.

[0071] Test Example 3

[0072] The tensile properties of the modified diaphragm and pure PP film substrate obtained in Example 1 and Comparative Example 1 were tested, and the test results are as follows: Figure 5 As shown in Table 1, where PP commercial film represents pure PP film matrix, PEGDA / PP represents Comparative Example 1, and 5wt% TiO2-PEGDA / PP represents Example 1;

[0073] Table 1. Tensile properties of the modified diaphragm and pure PP film substrate obtained in Example 1 and Comparative Example 1.

[0074] Tensile stress / MPa 15.39 15.00 13.49 strain / % 23.46 9.24 12.05

[0075] from Figure 5 As shown in Table 1, the tensile stress increased and the strain intensity decreased slightly after forming the PEO polymer network with PEGDA. However, the introduction of TiO2 nanoparticles not only strengthened the stress of the PP film but also increased the corresponding strain. This indicates that the combined effect of the PEO polymer network and TiO2 nanoparticles can significantly improve the mechanical properties of the PP film and enhance the dimensional stability of the PP film used in lithium batteries.

[0076] Test Example 4

[0077] The room temperature conductivity of the modified diaphragm and pure PP film substrate obtained in Example 1 and Comparative Example 1 was tested. The test method was as follows: the membrane sample was completely immersed in lithium hexafluorophosphate electrolyte for 6 hours, and then dried in a vacuum drying oven for 8 hours to completely dry the electrolyte (LiPF6 / EC / PC) on the membrane surface. The dried membrane was then cut into test pieces with a diameter of 2 cm and placed in a stainless steel fixture. The conductivity was obtained by measuring the resistance using a resistance meter. The lithium hexafluorophosphate electrolyte was made by uniformly mixing ethylene carbonate (EC) and polycarbonate (PC) at a volume ratio of 1:1, with a molar concentration of 1M.

[0078] The test results are shown in Table 2 and Figure 6As shown; where PP commercial film represents pure PP film matrix, PEGDA / PP represents comparative example 1, and 5wt% TiO2-PEGDA / PP represents example 1;

[0079] Table 2. Room temperature conductivity of the modified diaphragm and pure PP film substrate obtained in Example 1 and Comparative Example 1.

[0080] Temperature (°C) 30 30 30 Electrical conductivity (S / cm) <![CDATA[1.25×10 -3 ]]> <![CDATA[4.99×10 -4 ]]> <![CDATA[3.31×10 -5 ]]> Temperature (°C) 40 40 40 Electrical conductivity (S / cm) <![CDATA[1.36×10 -3 ]]> <![CDATA[5.77×10 -4 ]]> <![CDATA[3.82×10 -5 ]]> Temperature (°C) 50 50 50 Electrical conductivity (S / cm) <![CDATA[1.46×10 -3 ]]> <![CDATA[5.85×10 -4 ]]> <![CDATA[4.13×10 -5 ]]> Temperature (°C) 60 60 60 Electrical conductivity (S / cm) <![CDATA[15.1×10 -3 ]]> <![CDATA[7.45×10 -4 ]]> <![CDATA[6.88×10 -5 ]]> Temperature (°C) 70 70 70 Electrical conductivity (S / cm) <![CDATA[15.9×10 -3 ]]> <![CDATA[9.25×10 -4 ]]> <![CDATA[9.17×10 -5 ]]> Temperature (°C) 80 80 80 Electrical conductivity (S / cm) <![CDATA[1.66×10 -3 ]]> <![CDATA[9.80×10 -4 ]]> <![CDATA[1.08×10 -4 ]]>

[0081] from Figure 6 As can be seen from Table 2, after the adsorption of electrolyte, the conductivity of the film reinforced by the PEO polymer network structure and modified by TiO2 nanoparticles reached its maximum value at the same temperature.

[0082] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A modified diaphragm, characterized in that, It includes a polyolefin polymer film matrix and a polyethylene oxide polymer and titanium dioxide nanoparticles loaded on the polyolefin polymer film matrix; The polyethylene oxide polymer has a three-dimensional network structure; The method for preparing the modified diaphragm includes the following steps: A coating solution is prepared by mixing polyethylene glycol diacrylate, an initiator, a titanium source, a polar organic solvent, and water; the initiator is azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, hydrogen peroxide, potassium persulfate, or benzoyl peroxide. The coating liquid is coated onto the surface of a polyolefin polymer film substrate and then heat-treated to obtain the modified diaphragm.

2. The modified diaphragm according to claim 1, characterized in that, The loading percentage of the polyethylene oxide polymer is 1.878–3.878%; the loading percentage of the titanium dioxide nanoparticles is 0.256–0.356%.

3. The modified diaphragm according to claim 1, characterized in that, The polyolefin polymer film matrix includes PP film or PE film.

4. The method for preparing the modified diaphragm according to any one of claims 1 to 3, characterized in that, Includes the following steps: A coating solution is prepared by mixing polyethylene glycol diacrylate, an initiator, a titanium source, a polar organic solvent, and water; the initiator is azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, hydrogen peroxide, potassium persulfate, or benzoyl peroxide. The coating liquid is coated onto the surface of a polyolefin polymer film substrate and then heat-treated to obtain the modified diaphragm.

5. The preparation method according to claim 4, characterized in that, The mass of the initiator is 4 to 6% of the mass of the polyethylene glycol diacrylate.

6. The preparation method according to claim 4, characterized in that, The polar organic solvent includes acetone, acetonitrile, or chloroform; The ratio of polyethylene glycol diacrylate to polar organic solvent is 1g:150mL; The volume ratio of the polar organic solvent to water is 150:5 to 10.

7. The preparation method according to claim 4, characterized in that, The titanium source includes tetraethyl titanate, tetrabutyl titanate, titanium n-propoxide, titanium tetraisopropoxide, or titanium tetramethanol. The mass ratio of the titanium source to polyethylene glycol diacrylate is 0.22 to 0.62:

1.

8. The preparation method according to claim 4, characterized in that, The mixture includes: A first mixture is prepared by first mixing polyethylene glycol diacrylate, an initiator, and a polar organic solvent to obtain a first mixture. The first mixture is then mixed with water to obtain a second mixture. The second mixture and the third titanium source are mixed.

9. The preparation method according to claim 4, characterized in that, The heat treatment is performed at a temperature of 59–61°C for 5–6 hours.

10. The application of the modified separator according to any one of claims 1 to 3 or the modified separator prepared by the preparation method according to any one of claims 4 to 9 in lithium-ion batteries.

Citation Information

Patent Citations

  • Quasi-solid polymer electrolyte, preparation method and application thereof

    CN112904634A

  • Negative-electrode-free lithium battery with high energy density

    CN113964454A